EVALUASI SISTEM PENYIMPANAN OBAT DI UPT INTALASI FARMASI KABUPATEN BANJAR - Mochammad Maulidie Alfiannor Saputera; Afriatul Husna; Achmad Sarbini (Jurnal Insan Farmasi Indonesia, 2019)
Storage is an activity of storing and maintaining by placing drugs received in a place that is considered safe from theft and disturbances that can damage the quality of the drug. The purpose of this study was to find out whether the drug storage at the UPT Regency Pharmacy Installation Unit was in accordance with the Pharmaceutical Management Training Materials in District / City Pharmacy Installation, Directorate of Public Medication and Health Supplies, Directorate General of Pharmacy and Medical Devices Ministry of Health Republic of Indonesia in collaboration with Japan International Coorperation Agency (JICA) in 2010. This type of non-experimental research that is described in a deskritptive evaluative manner with prospective data collection. The population in the study of all drug storage rooms with a sample of the study was as many as 6 (six) drug chambers BUFFER and PKD. Data collection uses interview and direct observation methods. The research instrument using interview texts and observation forms. The results show that the preparation of storage facilities is 100% appropriate, the 90% spatial arrangement is appropriate, the preparation of the drug stock is 75% according to the observation of the drug quality 100% according to the standard.